Tumor suppression by control of matrix metalloproteinase recycling. (2nd November 2019) - Sneeggen, Marte; Schink, Kay O.; Stenmark, Harald
ABSTRACT: Secretion of matrix metalloproteinases (MMPs) enables cancer cells to degrade extracellular matrix, thus promoting tumor invasion and metastasis. We have recently found that the endosomal protein WDFY2 serves as a gatekeeper for MMP recycling from endosomes and that deletion of WDFY2, which is frequently lost in metastatic cancers, causes increased matrix degradation and cell invasion.